ANALISIS DETERMINAN IMPOR JAGUNG INDONESIA TAHUN 1987-2020 - Purba, Pinta Uli; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
This study analyzes the factors that are thought to affect Indonesia's corn imports, with the variables used being corn production, corn import prices, and Indonesia's foreign exchange reserves. Data was sourced from BPS, Bank Indonesia, IMF, and Kementerian Perdagangan with a research period from 1987 to 2020. The data obtained were analyzed using multiple linear regression analysis. From the regression results, it is found that corn production, corn import prices, and foreign exchange reserves have a significant effect on Indonesian corn imports simultaneously. The partial regression results found that corn import prices had a significant negative effect on Indonesian corn imports, while foreign exchange reserves had a significant positive effect on Indonesian corn imports. Meanwhile, corn production has no significant effect on Indonesian corn imports. Keywords: internastional trade, import, production, price, foreign exchange reserves.